PENGARUH SARANA DAN PRASARANA, HUBUNGAN SOSIAL DAN BUDAYA ORGANISASI TERHADAP MINAT MENGIKUTI PROSES DIKLAT ANGGOTA PADA MAPALA PELITA UNP KEDIRI - Malasari; Soeprajitno, Edy Djoko; Kurniawan, Rony (Universitas Nusantara PGRI Kediri, 2024)
This research is motivated by implementing management to achieve organizational goals. Mapala is an organization that operates in the field of love of nature and the environment. Mapala is influenced by the interest of its members in carrying out the training process. Infrastructure, social relations, and organizational culture can influence members' interest in carrying out the training process. This research aims to determine the influence of infrastructure, social relations and organizational culture on members' interest in participating in the training process at Mapala Pelita. This research uses a quantitative approach with a casual associative method. The sample consisted of 30 respondents who were taken using purosive sampling. The data obtained was processed and analyzed using linear multiple regression. The research results show (1) Facilities and Infrastructure (X1) have a significant effect on Interest (Y). (2) Social Relationships (X2) have a significant effect on Interest (Y). (3) Organizational Culture (X3) has a significant effect on Interest (Y). (4) Simultaneously Facilities and Infrastructure (X1), Social Relations (X2) and Organizational Culture (X3) have a significant influence on the Interest (Y) of Mapala Pelita's young members